(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This paper explores A. Suyarova’s Daughters of the Sun, a powerful narrative portraying the struggles and strength of Central Asian women. Through the lens of feminist literary criticism, the study investigates themes of identity, resilience, and cultural heritage. Drawing from textual evidence and socio-cultural analysis, the article highlights how Suyarova constructs female agency within a traditionally patriarchal society. This research contributes to understanding post-Soviet women’s literature and its role in reshaping gender discourse in modern Uzbekistan.